Self feeding cottonseed meal mixed with salt to steers as a protein supplement on bluestem grass. - Pickett, A.G.; Smith, E.F. (Kansas Agricultural Experiment Station, 2012)
Considerable interest has developed in the possibilities of self feeding a protein supplement to cattle on grass. Self feeding is a labor saving and eliminates the need for rounding up cattle every day. Under usual circumstances, it is impossible to control the amount of supplement consumed when it is self-fed. In an attempt to overcome this limitation a few cattlemen have self-fed a mixture of salt and cottonseed meal. It was found that the salt limited the amount consumed and that by varying the proportion of salt in the mixture it was possible to obtain the desired consumption of cottonseed meal. Preliminary tests were conducted in 1948-49 with two-year old steers on bluestem grass during the last 90 days of the summer grazing season and during the winter with one lot of yearling steers wintered on dry bluestem grass.
Keywords: Beef; Salt; Cottonseed; Protein; Bluestem grass